Sporidesmium guizhouense sp. nov. (Sordariomycetes incertae sedis), a new species from a freshwater habitat in Guizhou Province, China - Liu, Ling-Ling; Yang, Jing; Liu, Ning-Guo; Chen, Ya-Ya; Gui, Xiao-Xia; Liu, Zuo-Yi (Phytotaxa, 2019)
During a survey of freshwater fungi in Guizhou Province, China, a collection from a submerged decaying twig in Baihua Lake was identified as a new species of Sporidesmium sensu lato based on morphological characters and phylogenetic analyses of combined LSU, SSU, ITS, TEF1α and RPB2 sequence data. Phylogenetic analyses supported its placement in Sordariomycetes but the fungus grouped distant from Sporidesmium sensu stricto, and its ordinal or familial position within the class remained inconclusive. Sporidesmium guizhouense sp. nov. is introduced with an illustrated account and notes on its taxonomy, phylogeny and systematic position are provided.